MAL AND PLAZA, ADOPTED FROM URBAN SPACE - R.Siti Rukayah; Sugiono Sutomo; Joesron Alisyahbana (Jurnal Dimensi Seni Rupa dan Desain, 2007)
AbstractThe interior of retail concept always change from time to time due to increase requirement of human being to consume goods production. Concept mal in retail nowadays adopted from pedestrian mal, plaza and public square in urban design. So the function of mal was developed from shopping, space for gathering people, recreation and as new public space to net the consumen. But how is the mal as new public space if choosing location in public square like Sun pang Lima Semarang? The result of the research base on fenomenoloocal method, mal in public square, become a nice place for people to moving trhough, recreation and short traffict area. So the theory of designer interior that moving traffict is the most important matter in retail to determine its shop sealable or not and Marketing themy that suggest, location need to be correction.AbstrakKonsep ruang ritel selalu berkembang setiap saat sejalan dengan makin meningkatnya kebutuhan manusia dalam mengkonsumsi barang-barang produk. Konsep pada ritel ini diadopsi dari pedestrian ma!, plasa clan ruang publik, sehingga peranan mal dapat dikembangkan tidak saja sebagai tempat untuk berbelanja saja, tapi juga sebagai tempat untuk rekreasi dan untuk menarik pembeli